2007
DOI: 10.1007/s10681-007-9419-1
|View full text |Cite
|
Sign up to set email alerts
|

Flanking SSR markers for allelism test for the Asian rice gall midge (Orseolia oryzae) resistance genes

Abstract: Screening of rice germplasm against Asian rice gall midge, Orseolia oryzae (WoodMason), biotypes in India has led to identification of over 300 resistant rice genotypes. However, only ten resistance genes have been characterized so far. Identification of new genes through classical allelism test is tedious and time consuming. We propose to use closely linked flanking Simple Sequence Repeat (SSR) markers in allelism tests for identification of resistance genes. Of the ten known gall midge resistance genes, eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Recently the major QTL of AfRGM were located and validated [11], being the QTL with major effect (qAfRGM4) on chromosome 4. They could be easily incorporated into the parental lines of the promising hybrids through marker-aided backcrossing [33]. Knowledge on the distribution of virulent RYMV populations across different target sites will also help to deploy safely rice hybrids in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the major QTL of AfRGM were located and validated [11], being the QTL with major effect (qAfRGM4) on chromosome 4. They could be easily incorporated into the parental lines of the promising hybrids through marker-aided backcrossing [33]. Knowledge on the distribution of virulent RYMV populations across different target sites will also help to deploy safely rice hybrids in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…But their benefit in molecular breeding programs is yet to be realised because the markers were either genotype specific or dominant in nature or not very tightly linked. Codominant SSR markers are most suitable in marker-assisted breeding and have already been developed for Gm1 and Gm2 (Himabindu et al 2007) and their success in breeding programs has been demonstrated. But both the genes lack resistance to rice gall midge biotype4.…”
Section: Discussionmentioning
confidence: 99%
“…in different crop species. Many disease and insect pests resistance genes in rice have been tagged and mapped using microsatellite markers (Chen et al 2006;Fujita et al 2006;Gu et al 2004;Jena et al 2006;Sirithunya et al 2002;Xi-ming et al 2004) Tightly linked co-dominant SSR markers for Gm1 and Gm2 gall midge resistance genes have been developed (Himabindu et al 2007). Gm1 is resistant to biotypes 1, 3, 5, and 6 while Gm2 is resistant to biotypes 1, 2, and 5.…”
Section: Introductionmentioning
confidence: 99%
“…Classical allelism tests could not establish the identity of resistance genes in this breeding line. However, the novel molecular allelism test (Himabindu et al 2007) using linked markers revealed that the gene(s) in CR57-MR1523 is(are) nonallelic to the Gm1, Gm2 and Gm4. Further the single dominant gene in CR57-MR1523 conferring resistance to GMB4 may not be allelic to gall midge recessive gene gm3 and it may not be allelic to Gm8, which exhibits HR-type of reaction, conferring resistance to both GMB4 and GMB4M.…”
Section: Discussionmentioning
confidence: 99%
“…Once the tentative chromosome location was known, all the SSR markers on that particular chromosome were further analyzed in the selected 158 F 10 population showing clear 'R' and 'S' phenotype. The linked SSR markers for the genes Gm1, Gm2 and Gm4 were used for allelism test with the markers (Himabindu et al 2007) to predict the corresponding allele in CR57-MR1523.…”
Section: Dna Extraction and Pcrmentioning
confidence: 99%